The Maglemosian skeleton from Koelbjerg, Denmark revisited: identifying sex and provenance. Issue 1 (2nd January 2017) - Hansen, Jesper; Petersen, Hans Christian; Frei, Karin Margarita; Courtaud, Patrice; Tillier, Anne-marie; Fischer, Anders; Allentoft, Morten E.
ABSTRACT: The Koelbjerg individual, dated c . 8500 cal BC, represents the earliest human skeletal remains described from Scandinavia. Based on ancient DNA, strontium isotope and statistical anthropological analyses the individual's sex, haplogroup and geographical provenance are here analysed and discussed. In contrast to previous claims, our genetic and anthropological analyses show that this individual was a male. Additionally, the strontium isotope ratio of one of his first molars indicates that he most likely grew up locally.